Prevalence of underweight among preschool children attending anganwadi in Kannur district, Kerala, India - S. S., Anitha; Jayasree, A. K.; Antherjanam S., Devaki (International Journal Of Community Medicine And Public Health, 2017)
Background: Child malnutrition is an important indicator of the nutritional and health status of a country. Preschool children call for focused attention in India because India has the highest percentage of undernourished children in the world. The objective of this study was to estimate the prevalence of underweight among preschool children attending Anganwadi centers (AWC) in Kannur district, Kerala. Methods: Cross-sectional study done during July 2013- June 2014 among pre-school children (3-6 years) attending 44 AWC spread over eleven revenue blocks in the district. AWC were selected using multistage random sampling technique. Body weight of the children were measured and compared with WHO Growth standards. Mothers were interviewed using a pilot-tested semi-structured questionnaire. Data was entered in EpiData version 3.1 and analysis was done using the SPSS version 12. Results: The total number of 3-6 year old children included in the study was 456. The prevalence of underweight in the study population was found to be 17.3%. In this study, nutritional status of the child was found to have significant association (p<0.05) with the child’s birth weight and maternal educational status. Conclusions: Maternal educational status has a major role in prevention of underweight among preschool children. Child’s birth weight also influences their nutritional status.